ATP as a sympathetic neurotransmitter - Shatarat, Amjad (2011)
ATP has been shown to be a sympathetic neurotransmitter in blood vessels. However, its relative importance has been shown to be influenced by the experimental conditions employed such as alteration of the vascular tone. Thus the main aim was to raise the tone of vascular preparations and to further examine sympathetic neurotransmission in these preparations. Porcine whole mesenteries were perfused with physiological buffer and changes in pressure recorded or different sized mesenteric arteries were isolated and set up for isometric recording.